Mechanochemical Synthesis and Physicochemical Characterisation of Multicomponent Phases Comprising Lidocaine and Dicarboxylic Acids - Zotova, Julija (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2023)
Tuning of physicochemical properties of multicomponent phases incorporating active pharmaceutical ingredients (APIs) with counterions or coformers is a challenge that opens up unlimited possibilities for expanding applications and controlling biological activity of drugs. Mechanochemistry has been recognised as an optimal route for the synthesis of multicomponent phases as it eliminates the need for large volumes of solvents and purification steps, thus making it a sustainable alternative to conventional solution synthesis. In this work a range of multicomponent systems incorporating lidocaine (LID) and a series of unbranched aliphatic dicarboxylic acids as the counterions were synthesised by neat grinding and the effect of an alkyl chain length on the phase formation was investigated. The acids employed were structurally related aliphatic dicarboxylic acids with n carbon chain length, where n = 5-8: glutaric adipic, pimelic and suberic dicarboxylic acids. The systems obtained included a high-melting crystalline salt, a cocrystal, eutectics and ionic liquids. The evaluation of thermal and dynamic behaviours as well as crystallographic analysis of the systems was performed in an attempt to devise a prediction tool for structure-property relationship. Alternating trends in morphology, melting points, glass transition temperatures and crystallographic properties of the new phases were observed across the dicarboxylic acid series. The effect of changing LID and azelaic acid (n=9) ratios on the physicochemical properties of their corresponding multicomponent systems was also investigated using a thermodynamics-based approach. Microscopy, X-ray diffraction analysis, infrared spectroscopy, nuclear magnetic resonance, and thermogravimetric analysis provided complementary characterisation. Mechanochemical synthesis of LID:azelaic acid systems at a range of stoichiometries yielded at least two distinct liquid phases and two distinct crystalline phases, one of which involved a unique 2:3 LID:counterion composition not observed previously. Furthermore, the formation of oligomeric ionic liquids involving dicarboxylic acids has also been achieved for the first time. This investigation highlights the need for a careful and comprehensive characterisation of multicomponent systems, especially for pharmaceutical applications. The investigation of LID:long-chain dicarboxylic acid systems has shown that increasing length and flexibility of the long carbon backbone affect molecular recognition and crystallisation of new multicomponent phases. As a result of mechanochemical synthesis of LID with long-chain dicarboxylic acids, where n = 10?13, partial component ionisation was observed. The construction of thermodynamic phase diagrams provided evidence that H-bonding and partial proton transfer has led to solid eutectic formation in all the systems. However, no new crystalline multicomponent phases were obtained. The driving force for the multicomponent phase research is enhancement and optimisation of pharmaceutical outcome of the drugs. The influence of the observed structural variation of the LID:dicarboxylic acid systems synthesised on their stability, solubility, dissolution, lipophilicity, permeability and aggregation behaviour was evaluated. The even-odd alternating trends in physicochemical properties were also evident in the pharmaceutical attributes assessed. Incorporating LID within LID:dicarboxylic acid systems has significantly enhanced its solubility and dissolution parameters in the range of the systems investigated. The study of the systems comprising the entire range of dicarboxylic acids enhanced current understanding of the mechanisms of multicomponent phase formation and contributed to the advancement of a systematic approach for multicomponent phase discovery and development for pharmaceutical applications. In addition, the structure-property relationships were explored.
APPROVED
Keywords: ionic liquids; solid state; lidocaine; pharmaceutics